Comparative study of visual results obtained with two Trifocal lens models in cataract surgery - Alfredo Amigó-Francés; Alfredo Castillo-Gómez; David Carmona-González; Paula Martínez-Sorribes; Alfredo Amigó (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2020)
Purpose: To compare visual performance and Contrast Sensitivity (CS) outcomes, patient satisfaction and spectacle independence in patients implanted with two Models of trifocal Intraocular Lenses (MIOLs). Methods: This non-randomized prospective clinical study included 40 eyes of 20 patients undergoing cataract surgery with bilateral implantation of two different MIOLs, the trifocal Fine Vision MIOL (20 eyes) (PhysIOL, Liège, Belgium) and the trifocal Acriva Trinova MIOL (20 eyes) (VSY, Biotechnology, The Nederlands). Visual results, CS and patient satisfaction were evaluated 3 months after surgery.  Results: There was no statistically significant difference between groups regarding distance and intermediate visual acuity. Finevision showed better near visual outcomes than Acriva Trinova (p < 0.033). Both MIOLs provided similar CS within normal age ranges. Satisfaction test performed on uncorrected patients showed a variable presence of tolerable dysphotopsic phenomena with both MIOLs.  Conclusions: When postoperative emmetropia was achieved, both MIOLs provided good outcomes for distance and intermediate vision with no differences in contrast sensitivity. Fine Vision MIOL gave better near visual acuity results. There were tolerable dysphotopsic phenomena in both groups.